Profesionalitas Guru SMA Oku Selatan di Era New Normal Ditinjau dari Pengaruh Work Habits dan Disiplin Kerja - Ema Ema; Edi Harapan; Destiniar Destiniar (Journal on Education, 2023)
Work habits and work discipline of a group of individuals are two factors that influence the professionalism of OKU Selatan High School teachers in carrying out teaching assignments. In line with its objectives, this research examines the effect of these two variables on teacher professionalism in the new normal era. Quantitative methods are used with data collected through questionnaires and observation. Data analysis techniques using parametric statistics through linear regression testing. The results of the study succeeded in proving that partially work habits have a significant influence on the professionalism of teacher work. Likewise, work discipline has a significant influence on the professionalism of teacher work; In simultaneous testing it was found that in the new normal era, work habits along with work discipline had a significant influence on the professionalism of SMA teachers in OKU Selatan in carrying out teaching assignments.